Effect of fertilizer on coriander seed production - Kamrozzaman, MM; Ahmed, S; Quddus, AFMR (Bangladesh Journal of Agricultural Research, 2016)
A field experiment on coriander (Coriandrum sativum L.) was carried out during rabi seasons of 2011-12 and 2012-13 in Low Ganges River Flood Plain Soil under AEZ-12 at Farming System Research and Development Site, Hatgobindapur, Faridpur to find out optimum and economic doses of fertilizers for coriander (var. BARI Dhania 1) for sustainable higher yield and to update balanced fertilizer recommendation for target yield. The experiment was laid out in a randomized complete block design with 8 treatments viz. T1=N118P47K26S10Zn2.2B0.8 Kgha-1, T2= N147P47K26S10Zn2.2B0.8 Kg ha-1, T3= N147P59K26S10Zn2.2B0.8 Kg ha-1, T4= N147P47K32S10Zn2.2B0.8 Kgha-1, T5= N118P59K32S10Zn2.2B0.8 Kgha-1, T6= N147P59K32S10Zn2.2B0.8 Kgha-1, T7= N88P35K19S8Zn1.6B0.6 Kgha-1 and T8= Native nutrient (Control). The highest seed yield (1373 kg ha-1) was obtained from the treatment T3 which was statistically similar with T1, T2, T3, T4, T5 and T6 treatments. The soil test based treatment T1 produced 1311 kg yield ha-1 and yield difference of ther added fertilizer treatment with T1 was only 5%. The fertilizer added treatments didnt exert the significant difference with soil based treatment (T1) on yield and yield contributing characters. However, T1 treatment appeared to be the best suited combination because of its higher gross margin Tk 41,769 ha-1, capability in reducing nutrient cost Tk 13106 ha-1 and the highest marginal rate of return (MRR) (108%) whereas treatment T3 covered 21% MRR and the highest nutrient cost among the treatments and hence treatment, N118P47K26S10Zn2.2B0.8 Kg ha-1 (100% NPKSZnB from STB dose) may be recommended for coriander seed production in the study area. Bangladesh J. Agril. Res. 41(2): 345-352, June 2016